Simple Intraoperative Method for Administration of Local Antibiotic Powder in Orthopaedic Surgery - Zachary Reynolds, M.D.; Joshua Eskew, M.D.; Justin Vaida, M.D.; Michael Sridhar, M.D. (Arthroscopy Techniques)
Surgical site infections have a profound impact on patient outcomes and health care costs. Recent orthopaedic literature highlights the efficacy of using local antibiotic powder to mitigate these infections, particularly in high-risk orthopaedic cases such as open fractures and for patients with significant comorbidities. Often, particularly in deep surgical sites, it is difficult to get a sufficient amount of the powder to the targeted location. We describe a simple technique for much more precise antibiotic administration utilizing readily available supplies in the operating room, including a 10-cc syringe. This technique offers a straightforward and cost-effective means of administering antibiotic powder at specific locations to the surgical site without the frustration of powder loss from the wound.